The The Compressive Strength & Water Absorption of Chicken Egg Shell Concrete - Nuriman Nabila Yusman; Suraya Hani Adnan (Progress in Engineering Application and Technology, 2024)
Concrete products are widely utilised in the building and construction. Ordinary Portland cement (OPC), one of the basic materials, is often costly and emits carbon dioxide during manufacture. As a consequence of the social and environmental challenges of sustainability and energy conservation, the cement industry is urging it to reduce and partially replace cement production with supplemental cementing ingredients. Hence, this research aimed to determine the strength and the water absorption of the concrete with chicken eggshell powder. Eggshells are rich in nutrients and can be used as a substitute for cement that contains the main cementing element, calcium aluminate (CaAl2O4). The eggshell will outperforms cement due to its high concentration of multifunctional nutrients. The degree of workability was measured through the use of a slump test, and the percentage of water absorption, compressive strength, and ideal ratio of chicken eggshell powder included in the concrete mix design were determined by testing the concrete cubes after 7 and 28 days of age. In this study, powdered chicken egg shell was utilized in place of cement, substituting 10%, 20%, and 25% of the original cement. A total of 36 concrete cubes conducted tests for water absorption and compressive strength. As a result, the slump test outcomes for a 10% cement replacement in the concrete mix was within the range of the concrete slump design in between 50 mm to 100 mm slump for medium workability, showing a true slump with a collapse height of 70 mm. This percentage also shows the lowest water absorption rate compared to other percentages which is 2.31%. For compressive strength test, the ideal percentage for cement replacement is 20% as this percentage shows the exact characteristic strength with the concrete M30 grade compared to other percentage that does not achieve the desired strength. This shown that the optimum amount for concrete mix design is 10% and 20% cement replacement with powdered chicken eggshell. If the replacement rate is larger than 20%, additional additives must be added to the concrete mix to achieve a better result.